LEGAL UNDERSTANDING OF ENVIRONMENTAL LAW SUBJECT - Гаврилішин, Анатолій Петрович; Козирєва, Валентина Петрівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2021)
Purpose: current theoretical issues of the environmental law subject in Ukraine are considered, scientific concepts of the environmental legal relations subject are studied, the content of the subject is analyzed through the application of the Law of Ukraine «On Environmental Protection», authors’ scientific positions concerning the legal determination of the subject that which combines a set of conclusions on environmental safety, ownership, use, restoration of natural resources and environmental protection are proved. Scientific doctrines based on the principles of current environmental legislation, various concepts of scientific schools in the field of environmental law increase the role of science, academic discipline in this area. Methods: the study was conducted using such methods as analysis and comparison, synthesis. The methods of analysis and comparison were used in the study of scientific achievements of legal scholars to determine the subject of environmental law. Using the method of synthesis, the types of social relations in the field of use and reproduction of natural resources and environmental protection are established. Results: three groups of social relations are identified and it is concluded that the subject of environmental law includes natural resource, naturally protective and anthropo-protective social relations; the subject of Environmental Law is defined. Discussion: issues of legal understanding of Environmental Law subject in Ukraine. The authors conclude that the subject of environmental law is a system of integrated sub-branches of law, which includes legal norms governing public relations for the use of natural resources, their protection, reproduction, environmental safety, prevention and elimination of negative economic and other activities on the environment natural environment, conservation of natural resources, genetic fund of living nature, landscapes and other natural complexes, unique territories and natural objects. Although Ukrainian legislation is based on the priority of human and civil rights, freedoms and interests, the mechanism of their implementation, protection and provision should be improved by further systematization of environmental legislation taking into account the natural law doctrine of these rights, fundamentally new national state policy, rule of law.